Entrepreneurial Inclination Among Business Students: A Malaysian Study - Lim, Yet-Mee; Lee, Teck-Heang; Cheng, Boon-Liat (UI Scholars Hub, 2012)
Entrepreneurship has been the fundamental topics of discussion among the politicians, economists, and academics. Business creation is especially critical in developing countries to stimulate economic growth. The present study attempts to examine entrepreneurial inclination among students who are a potential source of entrepreneurs. The findings of the present research study indicate that majority of our business students are not entrepreneurial-inclined. They do not seem to possess strong entrepreneurial characteristics and entrepreneurial skills, and they are not keen in starting a new business. The roles of higher institutes of education and the government in promoting entrepreneurship are discussed.